Biodiversity of family Ditrichaceae Limpr of Kazakhstan (Eurasian Journal of Ecology, 2016)
The analysis of the moss family Ditrichaceae Limpr of Kazakhstan has been done. It was revealed a variety of mosses family Ditrichaceae, represented by 4 genera and 5 species. Among them in the Tien Shan revealed 5 species (including Ketmentau – 1, Ile Alatau – 3, and Kungei Alatau – 5 species) in the Aral- Caspian – 1 in Balkhash – 1, in central Kazakhstan – 1, in Junggar Alatau and Altai – 3 in each. First for Kazakh species of this family key – determinants are composed. The problems of ecology and geography were determined. In the flora of mosses family highlighted three environmental groups (mesophytes, xerophytes and xeromesophytes), with a predominance of mesophytes (50 % of total species). There were revealed only 2 geographic elements (arctic-alpine and cosmopolitan) with dominance ofarctic-alpine one (80 % of total species).
Keywords: family Ditrichaceae; mesophytes; xerophytes; xeromesophytes; arctic-alpine; cosmopolitan